Aplikasi Pestisida Nabati pada Budidaya Tanaman Cabai Merah (Capsium Annum L) di Desa Ujung Bandar, Kabupaten Langkat - Al Farizi; Maimunah Siregar (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
Chili has become a necessity for Indonesian people as an ingredient used as a cooking spice, thus making the demand for chili on the market very high. However, high market demand is often not matched by the supply of chilies on the market which is not sufficient to meet market needs. The lack of availability on the market is caused by several factors, one of which is crop failure caused by diseases and pests of chili plants. The first method of land processing is to loosen the land until it is fertile, after that it is sown with compost, usually with chicken, cow, and goat pui. After that, it is sprinkled and watered using a composter. The fertilizers used are synthetic and organic chemicals such as humic acid, trikoderma, PSE, and micro barter. Usually, the harvest produces an average of 300-500 grams per tree per cycle, not reaching 1 kg per tree in the harvest cycle. And some of the harvest is consumed and some is sold, and is usually sold through middlemen and to the market.